Population changes and primary healthcare delivery in Ebonyi State, Nigeria - Agatha Arochukwu; Felix Ike; Adelowo Adefisayo Adewoyin; Adebayo Oluwole Eludoyin (Discover Health Systems)
Abstract Background This study investigated  the impact of population dynamics on primary healthcare (PHC) delivery in Ebonyi State, Nigeria, with a focus on gender disparities, spatial distribution, and healthcare accessibility. The study employed Geographic Information System (GIS)-based spatial analysis to assess travel time and distance to PHC’s, ensuring equitable healthcare planning. Methodology A GIS-based Network Analyst tool and Tobler’s hiking function were applied to analyze accessibility to PHC under driving and walking scenarios. Primary data were collected from 170 PHC’s using the National Primary Health Care Development Agency’s checklist. Spatial data, including road networks and demographic statistics were obtained from the Ebonyi State Primary Health Care Development Agency and the National Population Commission. Results The population distribution across Ebonyi’s 13 Local Government Areas (LGAs) varied significantly. The most populated LGAs were Izzi, Onicha, Ikwo, and Ohaukwu; each  with approximately 300,000 people, while Ivo LGA contributed only 4.6%. Gender distribution was relatively balanced (51% female, 49% male), but Izzi and Ikwo LGAs possessed higher female populations, requiring specialized maternity and reproductive health services. Although 81.1% of the population can access a PHC within a 60-min drive (≤ 30 km), 37.9% of villages required over 60-min of walking, indicating underserved areas. The minimum standard checklist for 170 Primary Health Centers (PHCs) reveals that 90% of these centers are inadequately equipped with essential health facilities and personnel. As of 2022, only one PHC in Ebonyi State served a population exceeding 10,000, highlighting significant deficiencies in service coverage and resulting in disparities in both access and availability of healthcare services. Conclusion The study highlights spatial and demographic disparities in PHC accessibility, resource distribution, and service readiness across Ebonyi State, Nigeria. While most residents were within a 60-min drive of a PHC, rural areas faced significant access challenges due to poor infrastructure. The shortage of medical personnel and inadequate equipment further exacerbates healthcare inefficiencies. Addressing these gaps requires targeted resource allocation, PHC expansion, and infrastructural development to achieve Universal Health Coverage (UHC) and ensure equitable healthcare access across the state.